Carbon dioxide (CO2) emissions and economic growth: A systematic review of two decades of research from 1995 to 2017 - Mardani, Abbas; Streimikiene, Dalia; Cavallaro, Fausto; Loganathan, Nanthakumar; Khoshnoudi, Masoumeh (The Science of the total environment, 2019)
Understanding the nexus CO2 emissions and economic growth helps economies in formulating energy policies and developing energy resources in sustainable ways. Although during recent years, numerous of the previous studies have been very thoroughly investigated the nexus between economic growth and CO2 emissions, there is a lack of research regarding the qualitative systematic review and meta-analysis in these areas. The main purpose of this review paper is to present the comprehensive overview of the relationship between CO2 emissions and economic growth. In this regard, the Web of Science database has been chosen and a qualitative systematic and meta-analysis method which called “Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)” has been proposed. Therefore, a review of 175 published articles appearing in 55 scholarly international journals between 1995 and 2017 has been achieved to reach a broad review of the nexus between economic growth and CO2 emissions with other indicators. Consequently, the selected articles have been categorized by the author name, the year of publication, data duration, types of techniques, data analysis method, the name of indicators, country, scope (individual country and multi-countries), journals, results, and outcome in which they appeared. The results of this paper demonstrated that the nexus between CO2 emissions and economic growth gives reasons for policy options that have to reduce emissions by imposing limiting factors on economic growth as well. Given the fact that bidirectional causality exists, as far as economic growth increases or decreases, further CO2 emissions are stimulated in higher or lower levels and consequently, a potential reduction of the emissions should have an adverse influence on economic growth. [Display omitted] •A review of 175 articles dealing with CO2 and economic growth during 2 recent decades was performed.•These papers were obtained from 55 journals refereed at WoS database.•Qualitative systematic and meta-analysis method called “PRISMA” was applied.•Articles have been categorized by author, techniques, countries, data analysis, results, etc.•The bidirectional causality exists between economic growth and CO2 emission trends.